Food waste and shopping behaviour – quantitative household investigations based on local case studies from Germany - Jürgens, Ulrich (DIE ERDE – Journal of the Geographical Society of Berlin, 2022)
The connection between food waste and grocery shopping behaviour is investigated using a regional example from Ger- many. Quantitative surveys apply the food waste related lifestyle concept and multivariate analysis methods to identify four different attitude groups related to dealing with food in private households. The shopping patterns of these groups display a high degree of congruence with the attitude patterns. The retail formats and the food products purchased in them are investigated as the original source of food waste in private households, and waste-prone product types and reasons for disposal are explored. It is possible to identify the particular susceptibility of individual product groups to food waste, and also differences in the handling of food and food waste between the segmented groups of individuals. Originally fresh products dominate food waste. This can be linked to the material origins of these products that are pur- chased in both so-called alternative shops and in conventional retail formats. The identification of the attitude groups and behavioural groups allows relevant demographic structures that are not immediately obvious to be deduced. This can provide target groups for educational measures, for which reliance on a one-dimensional approach is insufficient.